2022
DOI: 10.3389/fcvm.2022.1016420
|View full text |Cite
|
Sign up to set email alerts
|

Counter pressure maneuvers for syncope prevention: A semi-systematic review and meta-analysis

Abstract: Physical counter pressure maneuvers (CPM) are movements that are recommended to delay or prevent syncope (fainting) by recruiting the skeletal muscle pump to augment cardiovascular control. However, these recommendations are largely based on theoretical benefit, with limited data evaluating the efficacy of CPM to prevent syncope in the real-world setting. We conducted a semi-systematic literature review and meta-analysis to assess CPM efficacy, identify literature gaps, and highlight future research needs. Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…Consistent with the present study, the results of a systematic review and meta-analysis by Williams et al . [ 24 ] show that physical counter-pressure maneuvers are a risk-free, cost-effective, and first-line management strategy for syncope prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present study, the results of a systematic review and meta-analysis by Williams et al . [ 24 ] show that physical counter-pressure maneuvers are a risk-free, cost-effective, and first-line management strategy for syncope prevention.…”
Section: Discussionmentioning
confidence: 99%
“…According to current guidelines ( 1 ), CPM are a class IIa recommendation for patients with syncope. While community trials show that these CPM can be beneficial ( 18 , 36 , 37 ), practical barriers are reported that limit their effective use in daily living ( 45 ). For example, during a squat, one must lower their center of mass, which requires mobility and strength about the hip, knee, and ankle joints.…”
Section: Discussionmentioning
confidence: 99%
“…This could be utilised in individuals who do not have sufficient prodrome, or are unable to effectively perform CPM. Indeed, one of the most highly reported barriers to employing CPM is the inability to identify an impending faint ( 45 ), and this has been noted by patients with and without a history of prodrome prior to their syncopal episodes ( 14 , 18 , 25 , 35 37 ). Similarly, there are distinct advantages of the subtlety of postural sway; CPM may not always be socially acceptable or desirable, and can be impractical in certain situations or occupations that require prolonged motionless standing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressor agents such as fludrocortisone and midodrine are routinely prescribed for OH and delayed BP recovery [ 60 ] despite their off-label use and potential side effects [ 61 ]. Perhaps increasing use of multicomponent intervention as well as training in physical counterpressure manoeuvres [ 62 ] would lessen the use of these medications and also benefit cases of combined supine hypertension and OH [ 63 ], where physical interventions can help both.…”
Section: Discussionmentioning
confidence: 99%